(untitled) (Journal of the Bangladesh Agricultural University, 2016)
Three botanical oils and of microbial derivatives an acaricide (Abamectin) were evaluated for their efficacy in controlling yellow mite Polyphagotarsonemus latus in the field laboratory of Entomology, Bangladesh Agricultural University, Mymensingh. The selected botanical oils viz. Neem oil, Mahogany oil and Karanja oil and the acaricide Ambush 1.8 EC were tested against jute yellow mite on standing jute plants of the experimental plots and assessed for their effect on the basis of population of the pest at 24, 48 and 72 hours after treatment and the reduction of yellow mite infested plant after 7 and 10 days of spraying. The acaricide Ambush 1.8 EC was highly effective showing reduction of 80.25% mite infested plant. Among the botanicals, Neem oil and Mahogany oil showed better efficacy and caused 60.55 % and 55.89 % reduction of mite infestation. Karanja oil was not found promising in controlling yellow mite of jute. Considering the effectiveness against the mite pest as well as the environmental safety, use of Neem and Mahogany oil and also the reduced risk acaricide, Ambush 1.8 EC might be suggested in the IPM of yellow mite. J. Bangladesh Agril. Univ. 14(1): 1-6, June 2016